Typical hierarchical processing in autistic adults. Issue 4 (18th May 2020) - Skripkauskaite, Simona; Slade, Lance; Mayer, Jennifer
ABSTRACT: Previous research suggests that autistic individuals exhibit atypical hierarchical processing, however, most of these studies focused solely on children. Thus, the main aim of the current study was to investigate the presence of atypical local or global processing in autistic adults using a traditional divided attention task with Navon's hierarchical figures. Reaction time data of 27 autistic and 25 neurotypical (NT) adults was analysed using multilevel modelling and Bayesian analysis. The results revealed that autistic, like NT, adults experienced a global precedence effect. Moreover, both autistic and NT participants experienced global and local interference effects. In contrast to previous findings with children, the current study suggests that autistic adults exhibit a typical, albeit unexpected, processing of hierarchical figures.